Coronavirus anxiety and the mental health in university students - Vivanco-Vidal, Andrea (2020)
The objective of the present study is to determine the relationship between anxiety by Covid - 19 and mental health in 356 university students (227 women and 129 men, average age = 22.36 years, Standard Deviation = 2.46). It also has as specific objectives to compare the anxiety by Covid - 19 and mental health according to sociodemographic variables. To whom it was applied the Coronavirus Anxiety Scale in Spanish and the Mental Health Inventory-5 (MHI). The study confirms that there is a statistically significant correlation between anxiety by Covid – 19 and mental health (ρ = −.67, p <.01). Also, regarding the comparisons made statistically significant differences are evidenced according to the variables sociodemographic previously mentioned. The study confirms that the more anxiety by Covid - 19 the lower mental health in a sample of Peruvians university students.